Virulence of Vibrio parahaemolyticus in Mud Crab (Scylla sp.) - Srimeetian, Pattarawadee; Suwanmala, Jitima; Tunkijjanukij, Suriyan (Journal of Mahanakorn Veterinary Medicine, 2017)
The study on virulence of Vibrio parahaemolyticus was challenged by experimental study against mud crab (Scylla sp.). The healthy mud crabs were injected with V. parahaemolyticus at 101-1010 CFU (Colony Forming Unit) per milliliter (ml). After injected for 1 day, the cumulative mortality of crabs was 100% at 108-1010 CFU per ml of bacteria. After injected for 2 days, the cumulative mortality was 100% at 107 CFU per ml of V. parahaemolyticus. During 30 days, the cumulative mortality was 22.22% at 106 CFU per ml of bacteria. Furthermore, during 30 days, the cumulative mortality was 0.00% at 105-101 CFU per ml of V. parahaemolyticus. This study suggesting that the virulence of V. parahaemolyticus causes for rapid mass mortality of mud crab.